Clinical Characterization of Genetically Diagnosed Cases of Spinocerebellar Ataxia Type 12 from India. Issue 1 (1st November 2017) - Choudhury, Supriyo; Chatterjee, Sayan; Chatterjee, Koustav; Banerjee, Rebecca; Humby, Jonathan; Mondal, Banashree; Anand, Sidharth S.; Shubham, Shantanu; Kumar, Hrishikesh
Abstract: View Supplementary Video 1 Background: Spinocerebellar ataxia type 12 (SCA12) is a rare form of an autosomal‐dominant ataxic disorder associated with an expansion of CAG repeat length. Here, we present a large case series of patients with SCA12 and describe a wide range of typical and rare symptoms. Methods: Twenty‐one consecutive patients with genetically proven SCA12 underwent detailed neurological examination. We assessed clinical characteristics using validated rating scales for evaluating motor features in SCA. Nonmotor symptoms and quality of life were assessed using appropriate, validated scales. Correlations of CAG repeat length with both severity score and age of onset were explored. Results: The mean age of onset was 51 years, and most patients were descendants of a single, endogamous Indian community (Agarwal). Tremor was the most common initial presenting symptom (90%). Hand dystonia was present in 14 of 21 patients, and most patients in the cohort presented with gait disturbance. Neuropsychiatric manifestations were common coexisting features. The CAG repeat length was significantly correlated ( r = −0.760; P = 0.0001) with early age of onset, but not with disease severity. Tremor affected the quality of life in 18 of 21 patients, because they had difficulty in handling liquids. Conclusions: Tremor was the most common, nonataxic symptom at initial presentation in patients with SCA12. Proximal upper limb tremor, typically with high amplitude and low frequency, can raise a strong diagnostic suspicion. Associated hand dystonia was a common coexisting motor feature. Various nonmotor features were also observed in several cases which require therapeutic attention. Abstract : View Supplementary Video 1